Analysis of viral DNA sequences in hamster cells transformed by herpes simplex virus type 2. - Galloway, D A (1980)
Herpes simplex virus type 2 (HSV-2) DNA was treated with four restriction endonucleases (EcoRI, HincIII, Bgl II, and Xba I) and eight fragments were purified and labeled with 32P in vitro. The kinetics of renaturation of each of the fragments was measured in the presence of DNA extracted from 333-8-9, a hamster cell line transformed by UV light-inactivated HSV-2 strain 333, and from a series of cloned derivatives and their tumor lines. All of the lines examined contained a partial set of viral sequences present at only a few copies per cell. Passage of the cell lines in tissue culture or in animals resulted in partial loss of viral DNA. Two blocks of sequences were present in most of the lines examined; those mapping at positions 21--33 of the HSV-2 genome were detected in seven of seven cell lines tested and those at positions 60--65 were detected in six of eight. Other sequences from the L component can also be present in the DNA of HSV-2-transformed hamster cells.